The contribution of overweight, obesity, and lack of physical activity to exit from paid employment: a meta-analysis - Suzan JW Robroek; Kerstin G Reeuwijk; Frances C Hillier; Clare L Bambra; Rogier M van Rijn; Alex Burdorf (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The objective of this review was to analyze systematically the association between overweight, obesity, and lack of physical activity (PA) and exit from paid employment through disability pension, unemployment, and early retirement. We also aimed to identify the influence of study population and study design on the magnitude of this association. METHODS: We searched PubMed and Embase for English language, longitudinal, quantitative studies that described the relationship between overweight, obesity, or lack of PA and exit from work. A short checklist was used to assess the internal and external validity of the studies. We first estimated the pooled effects using a random effects model and then analyzed the influence of study and population characteristics on associations by stratified meta-analyses. RESULTS: In total, 28 out of 1097 publications met the inclusion criteria. Obese [relative risk (RR)=1.53) and, to a lesser extent, overweight (RR=1.16) individuals had an increased likelihood of exit from paid employment through disability pension, but were not at statistically significant increased risk for unemployment or early retirement. Of 17 associations between a lack of PA and disability pension, 8 were statistically significant; this was also the case for 2 of 3 for unemployment. No associations were statistically significant for early retirement. CONCLUSIONS: Obesity is a risk factor for exit from paid employment through disability pension. There are also indications that a lack of PA is related to an increased risk of disability pension and unemployment. To protect workers against premature exit from paid employment, long-term interventions to prevent overweight and obesity and promote PA in the working population should be considered for implementation